PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizkya Rizkya; Yancik Syafitri (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
This study aims to determine the effect of the independent variables, namely capital structure, firm growth, firm size and profitability on firm value as the dependent variable. The research population includes property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. The sampling technique used is purposive sampling. Testing this hypothesis using multiple regression analysis with a significant level of 5% (0.05). The results of this study indicate that profitability has an effect on firm value while the capital structure of firm growth and firm size has no effect on firm value. keywords : capital structure, company growth, company size profitability and company value.